Wacana Berita PT. Djarum dan Bulu Tangkis Indonesia - Putranto, Teguh Dwi (Faculty of Communications Science, Dr. Soetomo University, 2019)
PT. Djarum as a company known as a cigarette producing company is doing one of the CSR program which is very contradictory. PT. Djarum seeks to distract people from the knowledge of the dangers of smoking by caring for the community through the Badminton support program. Or in other words Djarum Foundation provides CSR as compensation for guilt to the community. The purpose of this study is to know the construction of discourse on the CSR news PT. Djarum sports field especially Badminton. This research uses qualitative method by using Critical Discourse Analysis perspective which try to dismantle the structure of discourse in text. Researchers will take each of 2 news on every online portal (Tribunnews.com, Detik.com, and Kompas.com) in the period of 1 year starting from January 1, 2017 until December 31, 2017 so that there are a total of 6 news that will be examined.